A review on clogging of recirculating steam generators in Pressurized-Water Reactors. (May 2017) - Yang, Guangze; Pointeau, Véronique; Tevissen, Etienne; Chagnes, Alexandre
Abstract: Corrosion product deposits in the secondary side of nuclear power plant steam generators may result in Tube Support Plate (TSP) clogging and tube fouling. Magnetite has an inverse solubility above 150 °C, which favours iron precipitation when temperature increases. Flashing and electrokinetics are two strengthening processes for precipitation in TSP clogging. Surface chemistry of magnetite particles was discussed to understand its' interaction with TSP. Particle deposition by boiling was identified as the limiting process by performing numerical applications with nominal conditions. Guidelines drawn from this review for investigating specifically TSP clogging consist on conducting representative condition experiments and electrokinetics investigations. Graphical abstract: Highlights: A feedback analysis is discussed concerning SG tube fouling and TSP clogging. TSP clogging formation is governed by magnetite particle deposition and precipitation of soluble iron. Flashing and electrokinetic effects are potentially two strengthening processes for precipitation in TSP clogging. Deposition by boiling is found dominant in global particle deposition mechanism.